Web-Based Reservation System for Jubail Activity Center - Bahaisami, Mohsen Abdullah; ROZLINI BINTI MOHAMED (Applied Information Technology And Computer Science, 2023)
In this project a study has been conducted on the reservation system process at Jubail’s Activity Centre, located in Jubail, Saudi Arabia. Currently, the way that the reservation is implemented in the center is by manual documentation which usually leads them to face a few problems. This project is aimed to design a reservation system for the center through an object-oriented approach, develop it to be a web-based system accessed online on any device, and test the system as a whole to see the results. The system is being developed using the prototyping model of development. The system was expected to fix the main problems encountered in current system implementation, by having a reliable way of reserving the center’s facilities by the customers that that are using the system. With this system the goal is to make sure each customer’s information is correct or as reliable as possible.